Factor VII and thromboembolism - SARAÇOĞLU, AYTEN (ELSEVIER SCI LTD, 2018)
Recombinant activated factor VIIa (rFVIIa) is a potent hemostatic agent originally developed for the treatment of haemophilia patients with inhibitors against factor FVIII or FIX. In approved indications, the safety profile of rFVIIa is favourable without major concerns. The prevalence of thromboembolic (TE) complications is less than 4/100.000 with fatal events being extremely rare. Also, the majority of reported events occurred in elderly patients with predisposing factors for TE complications. Currently, off-label use of rFVIIa has become much more common with intracerebral haemorrhage and major surgical procedures being one of the most investigated areas. However, the literature had controversial results with a dubious safety profile. While in intracerebral haemorrhage and cardiac surgery the administration of rFVIIa appears to increase the risk for TE adverse events, in trauma patients, variceal bleeding and liver transplantation the risk doesn't seem to be higher. Besides, no significant difference was reported in mortality rates. Moreover, a close monitoring for signs and symptoms of TE episodes is essential in patients treated with rFVIIa, especially the elderly and other patients with predisposing risk factors for thrombosis. In this opinion article, we aimed to review the current literature about the potential TE adverse events of rFVIIa in different clinical and surgical scenarios. (c) 2018 Published by Elsevier Ltd.
Keywords: Recombinant activated factor VII; Thomboembolic events; Safety; NovoSeven (R); Haemorrhage; RECOMBINANT-FACTOR-VIIA; ACTIVATED FACTOR-VII; CELL-BASED MODEL; OFF-LABEL USE; ACUTE INTRACEREBRAL HEMORRHAGE; INHIBITOR BYPASS ACTIVITY; COAGULATION-FACTOR VIIA; FACTOR-IX INHIBITORS; DOSE FACTOR VIIA; CARDIAC-SURGERY